The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jhet.986
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrazolo[3,4‐b]pyridin‐6‐ones

Abstract: in Wiley Online Library (wileyonlinelibrary.com). The procedures for the synthesis of substituted pyrazolo[3,4-b]pyridine-6-ones and some of their properties are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…Aminopyrazoles have been widely reported to be synthesized via several methods [21][22][23][24][25][26][27][28]. Therefore, compound 1 was reacted with phenyl isothiocyanate/ethyl iodide, carbon disulfide/dimethyl sulfate, or differently 4substituted benzaldehyde derivatives to afford the corresponding acrylonitrile derivatives 3, 5, and 7a-c, respectively, which were further subjected to hydrazinolysis through their reaction with hydrazine hydrate 99% in ethanol to yield the target aminopyrazole derivatives 4, 6, and 8, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Aminopyrazoles have been widely reported to be synthesized via several methods [21][22][23][24][25][26][27][28]. Therefore, compound 1 was reacted with phenyl isothiocyanate/ethyl iodide, carbon disulfide/dimethyl sulfate, or differently 4substituted benzaldehyde derivatives to afford the corresponding acrylonitrile derivatives 3, 5, and 7a-c, respectively, which were further subjected to hydrazinolysis through their reaction with hydrazine hydrate 99% in ethanol to yield the target aminopyrazole derivatives 4, 6, and 8, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, structures 1 and 2 have attracted the interest of medicinal chemists due to the close similitude with the purine bases adenine and guanine, an interest that is clearly illustrated by the more than 300,000 structures 1 (5000 references, including nearly 2400 patents) and around 83,000 structures 2 (nearly 2700 references, including 1500 patents) included in SciFinder [ 4 ] and 180 reviews, including some on the synthesis of such structures [ 5 , 6 , 7 , 8 ]. These compounds present up to five diversity centers that allow a wide range of possible combinations of substituents capable of addressing different biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are only five specific reviews on pyrazolopyridines prior to this review. Three of them are devoted to the synthesis of such compounds [ 6 , 7 , 8 ], the most recent being from 2012 [ 6 ]. The other two cover biological aspects, either from a general perspective (a review from 1985, [ 16 ]) or a very specific point of view (kinase inhibitors, 2013 [ 17 ]).…”
Section: Introductionmentioning
confidence: 99%
“…[20~23] In addition, the carbonitrile group is also useful functional group and exhibits some applications in various synthetic transformations especially as a synthetic precursor to access amide and amine though the well-known Hofmethods for the pyrazolo [3,4-b]pyridine core have been reported, relying on condensation reactions of either 1,3-dicarbonyl or α,β-unsaturated carbonyl compounds with 5-aminopyrazoles, [24] or on the cyclization of hydrazines with appropriately substituted derivatives of nicotinic acid. [25,26] Recently, Aggarwal et al [27] reported an efficient method for synthesis of 4,7-dihydro-1H-pyrazolo [3,4-b]pyridine-5-nitriles by the condensation of 3-aryl-3-oxopropanonitriles and mono-substituted aryl/heteroarylhydrazines in ethanol in the presence of conc. HNO 3 .…”
Section: Introductionmentioning
confidence: 99%